Russian criminal culture among drug-addicted former soviet union immigrants in Israel. Issue 1 (2nd January 2019) - Liat, Yakhnich
ABSTRACT: This article explores the cultural context of substance abuse among drug-addicted Former Soviet Union (FSU) immigrants in Israel. Using a qualitative approach, it focuses on immigrant users' affiliation with the Russian criminal culture. The data analysis elicited a number of themes, including the key components of this culture, its attitude toward drug consumption, and its role in the users' lives and rehabilitation. It is argued that drug-addicted immigrants suffer multiple marginalization. Their affiliation with the ethnic criminal subculture serves as a defense reaction that protects their identities and grants them a sense of mastery not afforded in the wider society.